What Can We Learn from Financial Stability Reports? - Comelli, Fabio (IMF Working Papers; Working Paper ;, 2021)
This paper reviews the approaches to systemic risk analysis in 32 central bank financial stability reports (FSRs). We compare and contrast the systemic risk analysis in FSRs with the IMF Article IV staff reports, noting that Article IV staff reports and FSRs frequently pick up analytical content from each other. All reviewed FSRs include a systemic risk assessment, which has not always been the case in Article IV staff reports. Also, compared to Article IV staff reports, on average, FSRs tend to cover a wider range of financial risks and vulnerabilities and tend to have more extensive discussions of the policy mix to mitigate systemic risk. In these assessments, FSRs utilize sophisticated analytical tools, such as stress tests and growth-at-risk, more frequently than Article IV staff reports. We emphasize that a central bank FSR typically presents a rich resource that IMF country teams can leverage, as already done by some, in forming their independent view about systemic risk.